CITRA PEREMPUAN DAN KEKERASAN DALAM CERPEN LAILA KARYA PUTU WIJAYA - Rimadhani Fadilla Syarifa; Cintya Nurika Irma (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
This research aims to find out the image of women and violence in the short story Laila by Putu Wijaya. To find out how the portrayal of female characters by male authors, namely Putu Wijaya and to know what acts of violence happened to Laila. This research is qualitative research with descriptive methods. Data analysis techniques by reading repeatedly the short stories studied, describing the data according to the formulation of the problem used, interpreting the collected data, making conclusions, and the results of the description done. The results of this study are a picture of Laila's character. The image of a woman in Laila's character depicted with a hardworking, submissive and devoted woman to her husband and parents, and there is an act of violence committed by the character Romeo to Laila that is emotional violence. At the end of the story, Laila is physically and psychically free from her husband's cruelty but her heart and mind are not because there is no longer for her the way to heaven. Laila forgets when there are still many ways to go to Heaven because God is Most Merciful to every servant. Keywords : short stories, feminists, women’s image, Laila